2020
DOI: 10.1016/j.isci.2020.101429
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Our Own Body Influences Self-Concept and Self-Incoherence Impairs Episodic Memory

Abstract: How does our body affect the way we think about our personality? We addressed this question by eliciting the perceptual illusion that pairs of friends swapped bodies with each other. We found that during the illusion, the participants rated their own personality characteristics more similarly to the way they previously rated their friend's personality, and this flexible adjustment of self-concept to the ''new'' bodily self was related to the strength of illusory ownership of the friend's body. Moreover, a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…The SCR to bodily threat, a common implicit measure of body ownership, has previously shown to be stronger after synchronous than asynchronous stimulation in the rubber hand illusion and first-person perspective video-based full body illusions (i.e. Armel & Ramachandran, 2003;Petkova & Ehrsson, 2008;Petkova et al, 2011;Preuss & Ehrsson, 2019;Tacikowski et al, 2020). However, while we could evidence threat response in general, these responses were not modulated by experimental condition, which is in line with other studies using virtual avatars (Kokkinara & Slater, 2014;Slater et al, 2010).…”
Section: Sense Of Body Ownershipsupporting
confidence: 91%
“…The SCR to bodily threat, a common implicit measure of body ownership, has previously shown to be stronger after synchronous than asynchronous stimulation in the rubber hand illusion and first-person perspective video-based full body illusions (i.e. Armel & Ramachandran, 2003;Petkova & Ehrsson, 2008;Petkova et al, 2011;Preuss & Ehrsson, 2019;Tacikowski et al, 2020). However, while we could evidence threat response in general, these responses were not modulated by experimental condition, which is in line with other studies using virtual avatars (Kokkinara & Slater, 2014;Slater et al, 2010).…”
Section: Sense Of Body Ownershipsupporting
confidence: 91%
“…For example, attitudes toward other people change after illusory ownership of their bodies 29 , emotional feelings of social fear 42 and body dissatisfaction 32,33 can be modulated by the full-body ownership illusion, and the encoding of episodic memories depends on the embodied firstperson perspective 57 . Even beliefs about own personality characteristics 58 , the recognition of one's own face [59][60][61] , the style of one's own behavior 62 , and implicit associations with the past-self 45 are flexibly adjusted based on the ongoing perception of one's own body. With regard to gender, it has been shown that it is possible to induce the body-sex-change illusion 24,43 and that female participants who looked at male avatars from a first-person perspective improved their working memory performance during a stereotype-threatening situation 63 ; however, the latter finding needs to be interpreted with caution, as there was no conclusive evidence that the participants felt ownership of the avatar's body.…”
Section: Discussionmentioning
confidence: 99%
“…We had no reason to think that 1S could produce the strongest illusion (see introduction ), and since previous studies have demonstrated successful SCRs using a non-stimulated body part, albeit a body part that was stimulated in another experimental condition [ 7 ], we did not anticipate any issues relating to the choice of the left leg as the threat-targeted body part. The threat-evoked SCR procedure has successfully been used in many full-body illusion studies contrasting synchronous and asynchronous conditions [ 7 , 16 , 17 , 25 , 29 , 73 ] and in numerous works on the rubber hand illusion [ 27 , 74 76 ]. The main difference between these studies and the present study is the choice of body part in which to present the knife theat.…”
Section: Discussionmentioning
confidence: 99%
“…Each threat-evoked SCR was quantified as the magnitude in micro-siemens, μS, from the minimum to the maximum skin conductance level of the largest peak observed to onset a maximum of five seconds following the onset of the knife presentation [ 7 , 46 ]. Because these characteristic waveforms represent phasic changes in electrodermal activity that are time-locked to the onset of each knife stimulus, they are a well-founded representation of threat-evoked physiological responses [ 45 , 47 ] and, in turn, allow for a quantification of illusory ownership of the mannequin’s body [ 7 , 27 , 29 ].…”
Section: Methodsmentioning
confidence: 99%